L'e´mergence et la mise en forme du me´tier d'universitaire au Moyen-Age - Turmel, Andre (Canadian Journal of Higher Education, 1978)
At the dawn of the 12th Century a new type of intellectual life emerged in the wake of the urban activity that accompanied the beginnings of the mercantile economy. The university corporation became responsible for its recruitment and the organization of its activities, having gained its autonomy through a struggle with church and political establish-ments. The university teacher comes out as an intellectual craftsman, working with his specific skills and tools, and whose function it is to study and to teach. The praxis of the medieval university intellectual displays an ambivalent status in which characteristics of the worker and of the privileged alternate. Changes within the Church and the birth of States act upon the trade of the university scholar to transform it. Thus are gradually set the socio-economic conditions that will pave the way for the evolution leading from the medieval intellectual to the Renaissance humanist.